Farmers' food price volatility and Nigeria's growth enhancement support scheme - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
The prices of food in Nigeria have become considerably higher and more volatile since 2012. The aim of this research was to ascertain factors affecting farmers' involvement in the growth enhancement support programme (GESS) in the country. We ascertained the effect of the GESS on the handiness of market information and agricultural inputs that impact on price volatility at farm gate level. In number, 600 rural farmers were sampled across the six geopolitical zones of Nigeria. Results obtained from the use of a bivariate probit model show that farmers relied on the GESS for resolving food price volatility by making available the food market information and agricultural inputs that cut down the incidence and degree of panic-compelled price increment in Nigeria. The findings suggested the need to enhance the GESS in line with the agricultural transformation agenda (ATA) by reducing the hindrances mostly connected to the use of mobile phones, and how far the registration and collection centers are.
Keywords: O13; Q10; N27; 330; Agricultural transformation agenda; bivariate probit model; food price volatility; growth enhancement support scheme; rural farmers; Nigeria